Rare Cause of Seizures, Renal Failure, and Gangrene in an 83-Year-Old Diabetic Male - Stalin Viswanathan; Kandan Balamurugesan (Case Reports in Immunology)
We report an 83-year-old diabetic male who presented with acute-onset renal failure, seizures, psychosis, pneumonia, and right foot gangrene. Investigations revealed thrombocytopenia, CSF lymphocytosis, ANA and dsDNA positivity, hypocomplementemia, and pneumonitis following which he was treated with pulse methylprednisolone. He was treated for Pseudomonas-related ventilator-associated pneumonia, candiduria, and E. coli-related bedsore infection prior to discharge. He was discharged at request and died 17 days later due to a respiratory infection.